Boikoetliso Ba Boko (‘exercising the mind’): protocol for a mixed methods feasibility and acceptability study of a prototype mental health intervention for adolescents and young people with anxiety and depression - Hart, Claire; Desai, Rachana; Stuart, Lauren; Norris, Shane A. (Frontiers in Child and Adolescent Psychiatry, 2025)
BackgroundApproximately one in four adolescents in Sub-Saharan Africa experiences significantly elevated symptoms of anxiety and depression. Those living in resource-constrained communities face heightened risks due to acute distress, trauma, and less responsive health care services. Boikoetliso Ba Boko (meaning ‘exercising the mind’) is an intervention prototype designed for adolescents and young people experiencing common mental health conditions.MethodsThe prototype aims to implement a youth-centred community mental health intervention, through collaboration with existing public health systems and community resources. It seeks to enhance access to mental health support for adolescents and young people in Soweto, South Africa, by creating a dynamic and engaging therapeutic environment for those dealing with anxiety, depression, and suicidal ideation. This protocol outlines how we will evaluate the feasibility, acceptability, and implementation process of the prototype mental health intervention. We will enrol 200 at-risk adolescents and young people, aged 14–24 years, who will serve as their own controls, into the intervention and collect assessment and process evaluation data using mixed methods.DiscussionThis study aims to provide a comprehensive understanding of how the Boikoetliso Ba Boko adolescent mental health prototype can be effectively evaluated and scaled up in resource-constrained communities. The findings will inform the development of a Phase II randomized controlled trial protocol to assess the prototype's efficacy.EthicsEthical approval was granted by the Human Ethics Research Committee of the University of the Witwatersrand (M231045 MED23-09-040). Boikoetliso Ba Boko is registered with the Pan African Clinical Trial Registry (PACTR202409702283764).